Development of Phonics Teaching Instructional Material for English Teachers in Thailand - Khaengkhan, Anucha (ASEAN Journal of Education, 2024)
This study aimed to develop phonics instructional materials tailored for English teachers in Thailand to tackle specific pronunciation challenges encountered by Thai speakers of English. It utilized a mixed-methods research approach, integrating both quantitative and qualitative methodologies. The research sample consisted of 2,000 Thai individuals selected through stratified random sampling, ensuring diverse representation across various regions, age groups, and socioeconomic statuses, thus providing comprehensive coverage of the population’s phonetic challenges. Quantitative data were gathered through a structured survey designed to pinpoint specific pronunciation challenges at the alphabet, word, and phoneme levels, particularly focusing on sounds absent in the Thai language. Qualitative data were collected from 300 English teachers who implemented the developed phonics materials, "Phonics Focus" in their classrooms. These teachers provided feedback via reflection notes, which were analyzed to evaluate the effectiveness of the materials. The results revealed significant pronunciation difficulties, particularly at the alphabet and word levels, with 47% of participants encountering challenges at the alphabet level, 31% at the word level, and 22% with sounds not found in Thai. Additionally, rhythm analysis indicated a distinct preference for three-syllable English phrases across all age groups, with 92% of the surveyed population reporting a notable comfort level. Based on these findings, the "Phonics Focus" materials were developed, incorporating segments such as A to Z Phonics, AEIOU Phonics, and FIXED Phonics to address specific phonetic challenges. Feedback from teachers indicated high satisfaction, with the majority achieving competence level three or above in teaching English pronunciation using the newly developed phonics approach.